Sleep/wake behaviour of competitive adolescent athletes in New Zealand: insight into the impact of early morning training - Steenekamp, T.; Zaslona, J.; Gander, P.; Rowlands, D.; Signal, L. (Sleep Medicine, 2020)
13 swimmers (mean age 14.8 ± 1.4; 46% male) and 19 rowers (mean age 16.5 ± 1.1; all male) wore actigraphs and completed sleep diaries over a 2-week training period. Diaries included the Hooper Index and a question regarding device use before bed. Participants also completed chronotype questionnaires. Nights of the week were categorised as taking place before "morning training", "mornings off", "weekend mornings off", and "weekend morning training". Actigraphy and sleep diary variables were compared for different nights of the week. Results